THE INFLUENCE OF PRODUCT INNOVATION AND LOCATION ON BUSINESS COMPETITIVENESS ALMADANI JUARA CEMILAN IN PAJUS MARKET - Mariyotis Zebua; Ahmad Yudhira; Khamo Waruwu; Mella Yunita (Yayasan Amanah Nur Aman, 2026)
This research is motivated by the importance of micro-enterprise competitiveness in facing increasingly fierce competition, particularly for the Almadani Juara Snacks business in Pajus Market. The purpose of this study was to determine the effect of product innovation and location on business competitiveness. This study used a quantitative approach, collecting data through a questionnaire from 100 respondents who were Almadani Juara Snacks consumers, using an accidental sampling technique. Data analysis was performed using multiple linear regression. The results showed that product innovation had a partial significant effect on business competitiveness, with a calculated t-value of 4.804 > t-table 1.660 and a significance value of 0.000 < 0.05. Location also significantly influenced business competitiveness, with a calculated t-value of 3.062 > t-table 1.660 and a significance value of 0.003 < 0.05. Furthermore, product innovation was the most dominant variable influencing business competitiveness compared to location. Simultaneously, product innovation and location significantly influence business competitiveness. The discussion shows that increasing product innovation, such as flavor and packaging variations, along with strategic location selection, can increase consumer interest and maintain business sustainability. The conclusion of this study is that product innovation and location play a crucial role in enhancing the competitiveness of Almadani Juara Cemilan in Pajus Market.